Adrenal collision tumor: Renal carcinoma metastasis within adrenal adenoma - Reichert, Roberta; Schuch, Alice; Luersen, Gustavo Felipe (Clinical and Biomedical Research, 2015)
Collision tumors are defined as the presence of two contiguous histologically different lesions composed of benign and/or malignant components. They are infrequent entities and have been reported in various organs and systems. The most common type of collision tumor in the adrenal gland is the association of two benign lesions, adenoma and myelolipoma. Modification in image characteristics or unexpected growth of an adrenal tumor previously characterized as a benign lesion should be suspicious for collision tumor with a new aggressive component. In this article, we present a case of renal carcinoma metastasis within a previously known adrenal adenoma.